Correlation of hematological parameters with right-sided pleural effusion in pediatric dengue cases – A cross-sectional study - Gaddam, Harish; Tupalli, Rajashekar Reddy (Indian Journal of Child Health, 2019)
Background: Capillary leak in dengue presents as ascites, pleural effusion (PE), and pericardial effusion. Objectives: The objectives of the study were to correlate the hematological parameters with radiological findings in cases with right-sided PE. Materials and Methods: This was a cross-sectional study conducted at the tertiary care teaching hospital. A total of 138 cases were included in the study. Investigations included complete hemogram on the day of admission, day of diagnosis of PE and at discharge. Radiological investigations included chest X-ray, ultra-sonogram of abdomen, and chest which were correlated with hematocrit and platelet count. Results: Out of 138 cases, 71 (51%) had PE; out of which, 46 cases (64.78%) had bilateral effusions with right side more than left. About 21 (15.2%) cases had only right-sided PE. The mean platelet count and hematocrit were 67,640/?L and 31.8%, respectively, on the day of PE. Conclusion: In cases of dengue, right-sided PE is more common in cases with platelet count ranging between 20,000 and 50,000/?L.